Steroid bioaccumulation profiles in typical freshwater aquaculture environments of South China and their human health risks via fish consumption. (September 2017) - Liu, Shan; Xu, Xiang-Rong; Qi, Zhan-Hui; Chen, Hui; Hao, Qin-Wei; Hu, Yong-Xia; Zhao, Jian-Liang; Ying, Guang-Guo
Abstract: More attention was previously paid to adverse effects of steroids on aquatic organisms and their ecological risks to the aquatic environment. So far, little information has been reported on the bioaccumulative characteristics of different classes of steroids in cultured fish tissues. The present study for the first time provided a comprehensive analysis of the occurrence, bioaccumulation, and global consumers' health risks via fish consumption of androgens, glucocorticoids and progestanges in typical freshwater cultured farms in South China. The numbers and total concentrations of steroids detected in the tissues of five common species of the cultured fish were in the order of plasma > bile > liver > muscle and plasma > bile, muscle > liver, respectively. The field bioaccumulation factors for the detected synthetic steroids ranged from 450 to 97, 000 in bile, 450 to 65, 000 in plasma, 2900 to 16, 000 in liver, and 42 to 2600 in muscle of fish, respectively. This data suggests that steroids are bioaccumulative in fish tissues. Mostly important, 4-androstene-3, 17-dione (AED) and cortisone (CRN) were found to be reliable chemical indicators to predict the levels of steroids in plasma and muscle of the inter-species cultured fish, respectively. Furthermore, the maximum hazard quotients (HQs) of testosterone and progesterone were 5.8 × 10 −4 and 9.9 × 10 −5, suggesting that human health risks were negligible via ingestion of the steroids-contaminated fish. Graphical abstract: Highlights: Three classes of steroids were prevalent in aquaculture environments. Steroids are bioaccumulative in fish tissues. Tilapia has a high bioaccumulation potential for steroids in aquaculture farms. AED and CRN can be used as chemical indicators in plasma and muscle, respectively. Human health risks were negligible from ingestion of fish. Abstract : Most synthetic steroids were found bioaccumulative or very bioaccumulative in the bile, plasma, liver and muscle tissues of cultured fish.